2016
DOI: 10.1155/2016/8053860
|View full text |Cite
|
Sign up to set email alerts
|

Response of Pea Varieties to Damage Degree of Pea Weevil,Bruchus pisorumL.

Abstract: A study was conducted to determine the response of five pea varieties (Pisum sativum L.) to damage degree of Bruchus pisorum: Glyans, Modus, Kamerton, and Svit (Ukrainian cultivars) and Pleven 4 (Bulgarian cultivar). The seeds were classified into three types: healthy seeds (type 1), damaged seeds with parasitoid emergence hole (type 2), and damaged seeds with bruchid emergence hole (type 3) and they were sown. It was found that the weight of 1000 seeds did not affect the field germination of the pea varieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
3
5
0
Order By: Relevance
“…Plant performance was about 10% (growth) and 35% (shoot mass) higher for plants produced by beetle-infested seeds attacked by parasitoids than those from seeds infested with only beetles. Our results are in accordance with a study with the pea Pisum sativum (Nikolova 2016), in which they found that P. sativum seeds with beetle (Bruchus pisorum) emergence holes had lower germination, growth and seed production than control undamaged seeds and seeds with a parasitoid emergence hole. Conversely, Mateus et al (2011) found no difference in the germination rate and seedling growth between seeds (P. sativum) damaged by parasitized and unparasitized beetles (Bruchus pisorum).…”
Section: Effects Of Parasitoids On Seed Traits Plant Growth and Herbsupporting
confidence: 93%
See 1 more Smart Citation
“…Plant performance was about 10% (growth) and 35% (shoot mass) higher for plants produced by beetle-infested seeds attacked by parasitoids than those from seeds infested with only beetles. Our results are in accordance with a study with the pea Pisum sativum (Nikolova 2016), in which they found that P. sativum seeds with beetle (Bruchus pisorum) emergence holes had lower germination, growth and seed production than control undamaged seeds and seeds with a parasitoid emergence hole. Conversely, Mateus et al (2011) found no difference in the germination rate and seedling growth between seeds (P. sativum) damaged by parasitized and unparasitized beetles (Bruchus pisorum).…”
Section: Effects Of Parasitoids On Seed Traits Plant Growth and Herbsupporting
confidence: 93%
“…Thus, despite facilitating seed germination, the ultimate effect of beetle granivory for Lima bean plants may be detrimental. Most of the few other studies that have assessed seedling performance following seed predation by granivorous insects also found negative effects (Mack 1998, Mateus et al 2011, Fox et al 2012, Nikolova 2016). Our study not only adds to this knowledge but also reveals that the negative effects of seed predation on plant fate depend on a threshold set by a combination of the intensity of seed damage and the action of parasitoids that attack the seed beetles inside the seeds.…”
Section: Bottom-up Effects Of Pre-dispersal Seed Predation On Germinamentioning
confidence: 99%
“…Damaged seeds with parasitoid emergence holes, together with healthy seeds, provide a very good opportunity for growth and development while plants from damaged seeds with bruchid emergence holes had poor germination and vigor and low productivity (Nikolova, 2016b). It was concluded that these seeds cannot provide the creation of well-garnished seeding and stable crop yields.…”
Section: Losses Caused By Pea Weevilmentioning
confidence: 99%
“…Canada is the largest producer and exporter of dry pea, with an annual production of 4.9 million tonnes . However, field pea production is constrained by diseases and pests, resulting in significant economic losses . Improvement by conventional breeding is as old as agriculture itself, but, until recently, it has been limited to agronomic traits to achieve the desired results.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, field pea production is constrained by diseases and pests, resulting in significant economic losses. 8 Improvement by conventional breeding is as old as agriculture itself, but, until recently, it has been limited to agronomic traits to achieve the desired results. Crop breeding faces a number of challenges due to undesirable genetic linkages and limited knowledge exists for the genetic basis of disease resistance.…”
Section: Introductionmentioning
confidence: 99%